Parotid oncocytoma: Disease-free with a follow-up of three years after parotidectomy - Sookdee, Sirinkarn; Teeravanittrakul, Penmas (Journal of Medicine and Health Sciences, 2023)
Oncocytoma is a rare benign tumor and represents less than 1% of all salivary gland tumors. Most oncocytomas arise in the parotid gland and usually present as a solitary mass, indentified by nonspecific imaging and fine needle aspiration findings. The lesion is a diagnostic challenge for physician. However, diagnosis is confirmed by histopathology after parotidectomy. The prognosis was excellent. The subject was a 60-year-old man with left parotid gland swelling for a month. Imaging studies revealed a 2.3 cm homogeneous, moderately enhancing soft tissue density lesion over the anterior aspect of left parotid gland abutting the left masseter muscle. Fine needle aspiration showed a benign mixed tumor (suspected for pleomorphic adenoma). He was successfully treated with left total parotidectomy and sparing facial nerve surgery. The pathological report showed oncocytoma. Nowadays, the patient is disease free with a follow-up MRI of three years and no complications.